The Role of Interpersonal Communication in Early Marriage Couples in Forming a Happy and Prosperous Family in Medan Belawan District - Nasution, Lydia Nurhasanah; Nurbani, Nurbani; Humaizi, Humaizi; Kholil, Syukur; Kurniawati, Dewi (East Asian Journal of Multidisciplinary Research, 2024)
Interpersonal communication has a significant impact on the high rate of marriage among teenagers. This research aims to see the role of interpersonal communication in early marriage in forming a happy and prosperous family in Medan Belawan Village. The research method used is descriptive qualitative, collecting data through interviews, observations, and documents. The results showed that early marriages tend to be based on people with middle to lower economic conditions; interpersonal communication is essential in forming a happy and prosperous family. Effective communication between husband and wife is the primary key to understanding the needs, expectations, and values that underlie family relationships, especially in early marriage relationships.